Formação de formadores em contextos corporativos: uma abordagem crítico-colaborativa - Martins, Silvia Conceição Armada (2018)
This paper aims at understanding how the development of a critical reflective approach in corporate education teachers, can contribute to a developmental process that is reflected in conscious practices in teaching-learning. This research is situated in the field of Applied Linguists, as it seeks to understand the development and transformation of its participants through language. The theoretical framework of this paper is founded on the Social-Historical-Cultural Theory as discussed by Vygotsky ([1930] 2008; [1934] 2001), Leontiev(1977) and Luria (1977); on the concepts of ZPD as discussed by Vygotsky ([1930] 1991) and expanded by Engeström (2011), Magalhães (2009), Newman e Holzman (2014); on the studies of sense and meaning (VYGOYSKY, [1930]2008); on the investigations on critical reflection conducted by Schön (2000), Freire (1970), Smith (1992), Liberali (1994) e Magalhães (2004; 2007; 2009); and on the studies of collaborative argumentation discussed by Liberali (2013). According to Magalhães (2004; 2011), the critical development of teachers take place in collective and critical collaborative learning contexts, that allow means to effectively answer to problems in private contexts, as well as, give directions to transformative actions. Therefore, the Critical Collaborative Research (MAGALHÃES, 2011), was chosen to be the methodological basis of this study. The research was carried out on a business context in corporate education with three participants, the researcher and two focal participants. The data was collected in four audio recorded phases. On the first phase, a class of each participant was observed. Phases two and three were dedicated to reflective meetings involving all the participants and the researcher, phase four comprehends an individual reflective meeting, between the researcher and participant. The data was analysed considering the argumentative cathegories proposed by Liberali (2013), Bronckart ([1997] 1999), Brookfield and Preskill (2005), Orsolini (2005), Pontecorvo (2005) and Leitão (2011), and focused on the language used by the participants during the intervention moments with the objective to answer the research questions and understand if the development of a critical reflective attitude contributes to conscious practices in teaching-learning. This study’s results reveal that the environment of confidence in the reflective meetings, contributed to the creation of a collaborative context, allowing the construction of ZPDs, reflection and the reorganization of ideas and concepts. This movement allowed that new sense and meaning on conscious practices in teaching-learning, emerged in the discourse